A Preliminary Single-Cell RNA-Seq Analysis of Embryonic Cells That Express Brachyury in the Amphioxus, Branchiostoma japonicum - Satoh, Noriyuki; Tominaga, Hitoshi; Kiyomoto, Masato; Hisata, Kanako; Inoue, Jun; Nishitsuji, Koki (Frontiers in Cell and Developmental Biology, 2021)
Among chordate taxa, the cephalochordates diverged earlier than urochordates and vertebrates; thus, they retain unique, primitive developmental features. Especially, the amphioxus notochord has muscle-like properties, a feature not detected in urochordates and vertebrates. Amphioxus contains two Brachyury genes, AmphiBra1 and AmphiBra2, that are expressed in the blastopore, notochord, somites, and the tail bud. To distinguish expression profiles of the two genes in notochord at the single-cell level, we carried out single-cell RNA-seq (scRNA-seq) analysis using the amphioxus, Branchiostoma japonicum. This scRNA-seq analysis classified B. japonicum embryonic cells at stages from midgastrula to early swimming larva into 15 clusters. We first confirmed that cluster 8 comprises cells that express four myogenic factor genes to form somites. AmphiBra1 and AmphiBra2 were expressed mainly in cells of cluster 9, showing that this cluster comprises cells to form notochord. However, the two genes differed in expression level and in the embryonic regions in which they were expressed. In contrast to AmphiBra1, which was expressed at a moderate level in notochord, a high level of AmphiBra2 expression was detected in cluster 5 at late gastrula, and in clusters 4, 5, 8 (somite), and 9 (notochord) in neurula. Together with AmphiBra2, cells of clusters 4 and 5 expressed various developmentally relevant genes, including Wnt1, Wnt3, caudal, Hox1, and Hox3. Since these genes are expressed in blastopore and then tail bud, clusters 4 and 5 contain component cells of the tail bud. In addition, cells of clusters 4 and 5 expressed different sets of tool kit genes, suggesting that tail bud is composed of different cell types. This scRNA-seq analysis therefore highlights two Brachyury genes of amphioxus, and their differences in embryonic regions and levels of expression. It is highly likely that AmphiBra2 is an ortholog of Brachyury in amphioxus, expression and function of which are shared by other deuterostomes. On the other hand, Amphi-Bra1 is a duplicated copy and likely evolved a supplementary function for notochord formation in this lineage.